Mta modern teaching aids (the international school's resource book 2015) (Teaching aids Australia, 2015)
A comprehensive guide designed for educators in international school settings. This resource provides a wide array of teaching aids, strategies, and activities tailored to diverse learning environments. With a focus on fostering cross-cultural understanding and collaboration, the book equips teachers with innovative tools to enhance student engagement and academic success. Ideal for both new and experienced educators, this resource is essential for creating a dynamic and inclusive classroom.